Tracheostomy Complications in Institutionalized Children with Long-term Tracheostomy and Ventilator Dependence - Wilcox, Lyndy J; Weber, Brittany C; Cunningham, Tina D; Baldassari, Cristina M (Otolaryngology-head and neck surgery, 2016)
(1) To identify tracheostomy complications in institutionalized children with chronic tracheostomy. (2) To determine factors that predispose to development of tracheostomy complications in institutionalized children with chronic tracheostomy. Case series with chart review over 10 years. Tertiary children's hospital. Children were included if they underwent tracheostomy before 21 years of age and resided at a pediatric nursing facility. Most children were ventilator dependent and had severe comorbid medical conditions, including developmental delay and cerebral palsy. The number of tracheostomy complications and unplanned hospital admissions were recorded. Interventions for tracheostomy complications were also reviewed. Thirty-two institutionalized children with chronic tracheostomy were included. The mean age at time of tracheostomy was 5.4 years, with a mean duration of institutionalization of 9.1 years. Twenty-seven children (84%) experienced tracheostomy complications. The total number of complications was 79. The most common tracheostomy complications identified were peristomal granulation (n = 13) and suprastomal granulation (n = 12). Age at time of tracheostomy, duration of institutionalization, and ventilator dependence did not predict the likelihood of developing a complication. Of 32 patients, 20 were evaluated in the emergency room during the study, and there were 48 unplanned admissions for tracheostomy-related complications during the study. Forty-five urgent direct laryngoscopy and bronchoscopy procedures were performed in a total of 20 children with tracheostomy complications. Tracheostomy complications are common in institutionalized children with chronic tracheostomy and are challenging to manage. Further research is necessary to determine novel ways to reduce tracheostomy complications in this population.